2022
DOI: 10.2147/ijn.s343361
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Explores the Mechanism of Oxygen-Boosted Sonodynamic Therapy Based on All-in-One Nanobubbles to Enhance Ferroptosis for the Treatment of HCC

Abstract: Background The combination of sonodynamic therapy and oxygenation strategy is widely used in cancer treatment. However, due to the complexity, heterogeneity and irreversible hypoxic environment produced by hepatocellular carcinoma (HCC) tissues, oxygen-enhancing sonodynamic therapy (SDT) has failed to achieve the desired results. With the emergence of ferroptosis with reactive oxygen species (ROS) cytotoxicity, this novel cell death method has attracted widespread attention. Methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“… 160 In Chen et al’s research on the treatment of liver cancer by RSL3@O2-ICG NBs, essential genes were identified to affect the sensitivity of hepatocellular carcinoma to iron death. 158 In addition to molecular imaging techniques, such gene and protein level monitoring could be achieved by reporter imaging techniques that combined reporter proteins with corresponding imaging probes. 162 Because the reporter gene is inserted directly into the cell’s DNA, the imaging is generated only in the living cell and can retain accurate imaging for a long time as the cell divides and is passed on to daughter cells.…”
Section: Sonosensitizers Beyond Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“… 160 In Chen et al’s research on the treatment of liver cancer by RSL3@O2-ICG NBs, essential genes were identified to affect the sensitivity of hepatocellular carcinoma to iron death. 158 In addition to molecular imaging techniques, such gene and protein level monitoring could be achieved by reporter imaging techniques that combined reporter proteins with corresponding imaging probes. 162 Because the reporter gene is inserted directly into the cell’s DNA, the imaging is generated only in the living cell and can retain accurate imaging for a long time as the cell divides and is passed on to daughter cells.…”
Section: Sonosensitizers Beyond Imagingmentioning
confidence: 99%
“…Multiple studies have supported that multifunctional sonosensitizers could alter gene expression in cancer and immune-related cells and revealed therapeutic target genes in various signaling pathways by the data analysis. [158][159][160][161] For example, Wu et al designed IR820@NCP using RAS inhibitor Farnesyl-Thiosalicylic acid (FTS) to demonstrate that SDT combined with FTS predominantly achieved anti-tumour effects by inhibiting endothelial cells and simulating host immunity. 160 In Chen et al's research on the treatment of liver cancer by RSL3@O2-ICG NBs, essential genes were identified to affect the sensitivity of hepatocellular carcinoma to iron death.…”
Section: Sonosensitizers Beyond Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…It provided a novel clinical antitumor therapeutic strategy to induce ferroptosis via the consumption of GSH, disrupt redox balance by the Fenton reaction and doxorubicin-supplied hydrogen peroxide, synergistic cytotoxicity of doxorubicin inhibition of recurrence and metastasis of HCC, and reversing drug resistance in translational therapy. Chen et al 116 assessed the prospect of nanobubbles combined with SDT and ferroptosis for treating HCC. Because of their low immunogenicity, low cytotoxicity, and high biocompatibility, nanosized vesicle exosomes can be used as drug delivery systems.…”
Section: Nanotherapymentioning
confidence: 99%
“…In recent years, the combined treatment strategy of SDT and ferroptosis has been used in research on breast cancer and liver cancer. 17,23–26 However, its application in orthotopic brain tumors has not been studied.…”
Section: Introductionmentioning
confidence: 99%